Photocurable resin composition and method for manufacturing image display device
By using methylpropionate polymers with high hydroxyl value and no methylpropionate groups in the optical display device, combining monofunctional methylpropionate monomer, hydrogen extraction photopolymerizer and tackifier, the viscosity of the resin combination is adjusted, and the shrinkage and contact stress increase caused by crosslinking reaction in the existing photocuring resin combination is solved, and better adhesion strength and stretchability are achieved.
Patent Information
- Application Number
- JP2023088977
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-30
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2039-06-04
AI Technical Summary
The methylpropionate oligomer in the existing photocuring resin combination is prone to cross-linking reactions during the photocuring process, resulting in the shrinkage and contact stress of the resin layer, thereby reducing the adhesion strength and stretchability of the optical display device, especially when using easily deformed polycarbonate materials, the problem is more prominent.
The methylpropionate polymer is used, and its hydroxyl value reaches or exceeds 120 mgKOH/g and does not contain methylpropionate groups. It combines monofunctional methylpropionate monomer, hydrogen extraction photopolymerizer and tackifier to adjust the viscosity of the resin combination so that it reaches 10 mPa·s or above at 25°C and maintains 30 mPa·s or below at 60°C.
Through the improved photocuring resin combination, the adhesion strength and stretchability between the resin layer and the transparent optical material in the optical display device is significantly improved, suitable for high temperature environments, and maintain good spray performance under a wide range of spray temperature conditions.
Smart Images

Figure 0007656212000003 
Figure 0007656212000004 
Figure 0007656212000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a photocurable resin composition which has excellent adhesion to transparent optical materials such as glass, (meth)acrylic resins, and polycarbonates, can give a photocured product which exhibits good stretchability, and is preferably applicable to an inkjet coating method. [Background technology]
[0002] Incidentally, liquid crystal display devices and organic EL devices are widely known as image display devices in which a light-transmitting cover member such as a transparent cover material and an image display member such as a liquid crystal display panel are laminated via a photocurable resin layer. In these image display devices, at least the opposing surfaces of the light-transmitting cover member and the image display member that sandwich the photocurable resin layer are each made of a transparent optical material. Conventionally, such image display devices are manufactured by applying a photocurable resin composition to one surface of either a flat image display member or a light-transmitting cover member by a die coating method, a screen coating method, or the like to form a photocurable resin composition film, irradiating the photocurable resin composition film with ultraviolet light to provisionally cure it to form a provisionally cured resin layer, laminating the other member on the provisionally cured resin layer, and irradiating ultraviolet light from the light-transmitting cover member side to fully cure the provisionally cured resin layer.
[0003] In recent years, curved image display devices have come onto the market, and coating has come to be carried out on image display members or light-transmitting cover members that are curved into shapes such as a gutter shape, a bowl shape, etc. In this case, it is necessary to apply the photocurable resin composition relatively thickly to the center of the image display member or light-transmitting cover member, and gradually apply it thinner toward the periphery, so instead of the conventional die coating method or screen coating method, it has been proposed to apply the photocurable resin composition to the image display member or light-transmitting cover member by an inkjet coating method that can easily set the amount of ink applied for each fine region (Patent Document 1).
[0004] In Patent Document 1, in order to apply an inkjet coating method to the production of an image display device, the photocurable resin composition used contains, in addition to a monofunctional (meth)acrylate monomer, a (meth)acrylate oligomer having a (meth)acryloyl group and a molecular weight of 5,000 or more, and further contains a photo or thermal radical polymerization initiator, and is an acrylic photocurable resin composition whose viscosity is adjusted to 150 mPa s or less, specifically 27 to 141 mPa s (25°C) (see Examples). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-210578 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the photocurable resin composition used in Patent Document 1 has a problem that the (meth)acrylate oligomer contained therein has a (meth)acryloyl group, and thus a crosslinking reaction occurs during photocuring, resulting in curing shrinkage. For this reason, when a light-transmitting cover member and an image display member are laminated with a photocurable resin layer made of such a photocurable resin composition, there are problems in that stress due to curing shrinkage of the photocurable resin layer occurs at the interface between the photocurable resin layer and the light-transmitting cover member and / or the interface between the photocurable resin layer and the image display member, resulting in a decrease in interfacial adhesion strength, and problems in that stretchability for alleviating the stress occurring at the interface when the image display device is deformed is decreased. These problems tend to be prominent when polycarbonate, which is easily deformed in a high-temperature environment, is used as a transparent optical material used in the image display device.
[0007] The present invention is intended to solve such conventional problems, and has an object to provide a photocurable resin composition that does not cause problems such as a decrease in interfacial adhesion strength or a decrease in extensibility that are derived from the use of a (meth)acrylate oligomer having a (meth)acryloyl group, as a photocurable resin composition to be applied using an inkjet coating method when manufacturing an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocured resin layer formed from a photocurable resin composition. [Means for solving the problem]
[0008] The present inventors have found that the above-mentioned objects can be achieved by using a (meth)acrylate polymer having a hydroxyl value of a predetermined value or more and having no (meth)acryloyl group, instead of a (meth)acrylate oligomer having a (meth)acryloyl group, as a polymeric substance to be used in combination with a (meth)acrylate monomer constituting a photocurable resin composition, using a hydrogen abstraction type photopolymerization initiator as a photopolymerization initiator, and further adjusting the viscosity of the photocurable resin composition to 10 mPa·s or more at 25°C and 30 mPa·s or less at 60°C, and then using a tackifier in combination, thereby completing the present invention.
[0009] That is, the present invention relates to a photocurable resin composition that can be applied to an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocurable resin layer formed from the photocurable resin composition, the photocurable resin composition comprising the following components (A) to (D): <Component (A)> A (meth)acrylate polymer having a hydroxyl value of 120 mgKOH / g or more and having no (meth)acryloyl group; <Component (B)> Monofunctional (meth)acrylate monomer; <Component (C)> Hydrogen abstraction type photopolymerization initiator; and <Component (D)> Tackifier; Contains the content of the tackifier of component (D) in the photocurable resin composition is 1 to 9 mass %, The photocurable resin composition has a viscosity of 10 mPa·s or more at 25°C and 30 mPa·s or less at 60°C.
[0010] The present invention also provides a method for producing an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocured resin layer formed from a photocurable resin composition, the method comprising the steps of: <Process (a)> A step of ejecting the photocurable resin composition of the present invention from a nozzle of an inkjet coating device onto a surface of either an image display member or a light-transmitting cover member to form a photocurable resin composition film; <Process (b)> A step of laminating another member on the photocurable resin composition film and bonding the image display member and the light-transmitting cover member; and <Process (c)> a step of irradiating the photocurable resin composition film sandwiched between both panels with ultraviolet light to cure the film, thereby obtaining an image display device in which the image display member and the light-transmitting cover member are laminated with a photocurable resin layer; The present invention provides a method for producing the same.
[0011] The present invention also provides a method for producing an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocurable resin layer formed from a photocurable resin composition, the method comprising the steps of: <Process (aa)> A step of discharging the photocurable resin composition of the present invention from a nozzle of an inkjet coating device onto a surface of either an image display member or a light-transmitting cover member to form a photocurable resin composition film; <Process (bb)> A step of irradiating the photocurable resin composition film with ultraviolet light to form a provisionally cured resin layer; <Process (cc)> A step of laminating another member on the provisionally cured resin layer and bonding the image display member and the light-transmitting cover member; and <Process (dd)> The present invention provides a manufacturing method that includes a step of irradiating a provisionally cured resin layer sandwiched between two panels with ultraviolet light to fully cure the resin, thereby obtaining an image display device in which an image display member and a light-transmitting cover member are laminated with a photocured resin layer. Effect of the Invention
[0012] The photocurable resin composition of the present invention is a photocurable resin composition that can be applied to an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocurable resin layer formed from a photocurable resin composition, and as a component to be used in combination with a monofunctional (meth)acrylate monomer that is a main polymerization component, a (meth)acrylate polymer having a hydroxyl value of 120 mgKOH / g or more and no (meth)acryloyl group is used instead of an oligomer having a (meth)acryloyl group that can polymerize with the monomer, and a hydrogen abstraction type photopolymerization initiator is used as a photopolymerization initiator. Such a (meth)acrylate polymer does not contribute to photopolymerization based on the (meth)acryloyl group, but hydrogen is abstracted by the hydrogen abstraction type photopolymerization initiator to generate radicals, and as a result, it is incorporated as a side chain or a polymer crosslinking chain into the polymerization chain formed from the (meth)acrylate monomer, and can impart good plasticity, film-forming property, and adhesiveness to the photocurable resin composition.
[0013] Furthermore, the photocurable resin composition of the present invention contains a tackifier, which can improve the interfacial adhesion strength of the photocured product of the photocurable resin composition of the present invention to transparent optical materials such as glass and polycarbonate, and can also improve the stretchability.
[0014] Furthermore, the photocurable resin composition of the present invention has a viscosity of 10 mPa s or more at 25°C and 30 mPa s or less at 60°C, and therefore exhibits good suitability for inkjet coating under a wide range of inkjet coating temperature conditions, including 25°C and 60°C. [Brief description of the drawings]
[0015] [Figure 1]FIG. 1 is an explanatory diagram of step (a) of the method for producing an image display device of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram of step (a) of the method for producing an image display device of the present invention. [Diagram 3] FIG. 3 is an explanatory diagram of step (b) of the method for producing an image display device of the present invention. [Figure 4] FIG. 4 is an explanatory diagram of step (b) of the method for producing an image display device of the present invention. [Diagram 5] FIG. 5 is an explanatory diagram of step (c) of the method for producing an image display device of the present invention. [Figure 6] FIG. 6 is an explanatory diagram of step (aa) of the method for producing an image display device of the present invention. [Figure 7] FIG. 7 is an explanatory diagram of step (aa) of the method for producing an image display device of the present invention. [Figure 8] FIG. 8 is an explanatory diagram of step (bb) of the method for producing an image display device of the present invention. [Figure 9] FIG. 9 is an explanatory diagram of step (bb) of the method for producing an image display device of the present invention. [Figure 10] FIG. 10 is an explanatory diagram of the step (cc) of the method for producing an image display device of the present invention. [Figure 11] FIG. 11 is an explanatory diagram of step (dd) of the method for producing an image display device of the present invention. [Figure 12] FIG. 12 is an explanatory diagram of step (dd) of the method for producing an image display device of the present invention. [Figure 13] FIG. 13 is a bar graph comparing the interfacial adhesion strength of the cured products of the photocurable resin compositions of Examples 1 to 4 and Comparative Example 1 to polycarbonate. [Figure 14] FIG. 14 is a bar graph comparing the interfacial adhesion strength to glass of the cured products of the photocurable resin compositions of Examples 1 and 4 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, first, the photocurable resin composition of the present invention will be described, and then a method for producing an image display device using the photocurable resin composition will be described.
[0017] <Photocurable resin composition> The photocurable resin composition of the present invention is preferably applicable to an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting cured resin layer formed from the photocurable resin composition, and contains the following components (A), (B), (C), and (D), and has a viscosity of 10 mPa s or more at 25°C and 30 mPa s or less at 60°C.
[0018] The image display device to which the photocurable resin composition of the present invention can be preferably applied, and the image display member and light-transmitting cover member constituting the image display device will be described together with the description of the manufacturing method of the image display device of the present invention.
[0019] <Component (A)> The photocurable resin composition of the present invention contains a (meth)acrylate polymer having a hydroxyl value of 120 mgKOH / g or more, preferably 170 mgKOH / g or more, and having no (meth)acryloyl group, in order to provide plasticity to the cured product and ensure good film-forming properties (film-forming maintenance) and adhesiveness. Having a hydroxyl value indicates having a hydroxyl group in the molecule, and having a hydroxyl group enables bonding to a side chain of a polymer chain in cooperation with the hydrogen abstraction type photopolymerization initiator of component (D) described later. In this specification, "(meth)acrylate" is a term that includes acrylate and methacrylate.
[0020] With respect to the (meth)acrylate polymer of component (A), the hydroxyl value is the mass (mg) of KOH required to neutralize the acetic acid generated by hydrolyzing the acetyl group after acetylating the hydroxyl group in 1 g of the polymer. Therefore, the larger the hydroxyl value, the more hydroxyl groups there are. The reason why the hydroxyl value of the (meth)acrylate polymer of component (A) is set to 120 mgKOH / g or more is that if it is less than 120 mgKOH / g, the crosslink density of the cured product of the photocurable resin composition is low, and the decrease in elastic modulus, especially at high temperatures, tends to be significant. If the crosslink density of the cured product is simply increased, the polyfunctional (meth)acrylate monomer of component (E) described later may be used in large amounts, but there is a concern that the cured product of the photocurable resin composition may become brittle. Therefore, by crosslinking with a polymer having a certain molecular weight, it is possible to impart good flexibility and cohesive strength to the cured product. Therefore, if the hydroxyl value is too high, the crosslink density of the cured product of the photocurable resin composition becomes too high and flexibility tends to be lost, so the hydroxyl value is 400 mgKOH / g or less, preferably 350 mgKOH / g or less.
[0021] The reason for using a (meth)acrylate polymer of component (A) that does not have a (meth)acryloyl group is to prevent the (meth)acryloyl group from being excessively incorporated into the main chain of the polymerization chain composed of the (meth)acrylate monomers of components (B) and (C), since the presence of the (meth)acryloyl group increases the possibility of the group being excessively incorporated into the main chain of the polymerization chain composed of the (meth)acrylate monomers of components (B) and (C).
[0022] The weight-average molecular weight Mn of the (meth)acrylate polymer of component (A) is preferably 5000 or more, more preferably 100000 or more, since if it is too small, the number of molecules without hydroxyl groups introduced increases and the risk of bleeding and the like tends to increase, whereas if it is too large, the viscosity increases and ejection failure tends to occur, so it is preferably 500000 or less, more preferably 300000 or less. In this specification, the weight-average molecular weight Mw and number-average molecular weight Mn of the polymer can be measured by gel permeation chromatography (GPC) (based on the molecular weight of standard polystyrene).
[0023] In addition, the polydispersity (Mw / Mn) of the (meth)acrylate polymer of component (A) is preferably 3 or more since if it is too low, the polymer and unreacted monomers tend to separate easily, and if it is too high, undesirable relatively low molecular weight polymer components are mixed in, so it is preferably 10 or less.
[0024] A preferred example of the (meth)acrylate polymer of component (A) is a copolymer of a hydroxyl group-containing (meth)acrylate monomer and a hydroxyl group-free (meth)acrylate monomer. It is preferably liquid at room temperature. Although a homopolymer of a hydroxyl group-containing (meth)acrylate monomer can also be exemplified, the polarity of the polymer tends to be too high, resulting in a high viscosity liquid or solid at room temperature, and there is a concern that the compatibility with other components may decrease.
[0025] The hydroxyl group-containing (meth)acrylate monomer, which is a monomer unit constituting the (meth)acrylate polymer of component (A), is a (meth)acrylate having one or more hydroxyl groups in the molecule, and specifically includes 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-chloropropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, ethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, propylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, cyclohexyl dimethanol mono(meth)acrylate, etc. Among them, 2-hydroxyethyl (meth)acrylate is preferably exemplified in terms of polarity control and price.
[0026] As the hydroxyl group-free (meth)acrylate monomer capable of constituting the (meth)acrylate polymer of component (A), for example, a monofunctional (meth)acrylic acid alkyl ester having a straight chain or branched alkyl group with 1 to 18 carbon atoms is preferable, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, tridecyl (meth)acrylate, and the like.
[0027] A particularly preferred example of the (meth)acrylate polymer of component (A) is a copolymer of 2-hydroxyethyl acrylate and 2-ethylhexyl acrylate, from the viewpoints of availability and feasibility of achieving the effects of the invention. Isobornyl acrylate may be further copolymerized.
[0028] The content of the (meth)acrylate polymer of component (A) in the photocurable resin composition is preferably 1% by mass or more, more preferably 10% by mass or more, since if it is too small the composition tends to become brittle, whereas if it is too large the composition tends to have a tendency to cause poor ejection due to an increase in viscosity, so the content is preferably 55% by mass or less, more preferably 45% by mass or less.
[0029] <Ingredient (B)> The photocurable resin composition of the present invention contains a monofunctional (meth)acrylate monomer as a polymerization component. The monofunctional (meth)acrylate monomer can be appropriately selected from known monofunctional (meth)acrylate monomers, taking into consideration the intended use of the photocurable resin composition and the physical properties to be realized. The content of the monofunctional (meth)acrylate monomer of component (B) in the photocurable resin composition varies depending on the type of monomer, but if it is too small, there is a concern that the interfacial adhesion strength will be insufficient, and if it is too large, there is a concern that the stretchability will decrease. Therefore, the content is preferably 30% by mass or more, more preferably 60% by mass or more, preferably 90% by mass or less, and more preferably 80% by mass or less.
[0030] In addition, the monofunctional (meth)acrylate monomer of component (B) may have a reduced compatibility with the (meth)acrylate polymer of component (A) having a hydroxyl value of 120 mgKOH / g or more and no (meth)acryloyl group after curing, resulting in the photocured resin layer becoming cloudy, depending on the type. For this reason, it is preferable to use a hydroxyl-containing monofunctional (meth)acrylate containing one or more hydroxyl groups, preferably one hydroxyl group, as the monofunctional (meth)acrylate monomer of component (B), since it has a high affinity with the (meth)acrylate polymer of component (A) containing a hydroxyl group and is expected to improve reliability in a high-temperature and high-humidity environment. In this case, it is preferable to use a non-hydroxyl-containing (meth)acrylate in combination in order to set the adhesion and viscosity of the cured product of the photocurable resin composition to a good range. That is, it is preferable that the monofunctional (meth)acrylate monomer of component (B) is composed of a hydroxyl group-containing monofunctional (meth)acrylate monomer of component (B1) and a hydroxyl group-free monofunctional (meth)acrylate monomer of component (B2).
[0031] Specific examples of the hydroxyl group-containing monofunctional (meth)acrylate monomer of component (B1) include the same monomers as the hydroxyl group-containing (meth)acrylate monomers capable of constituting the (meth)acrylate polymer of component (A). Among them, at least one selected from 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate is preferred, with 4-hydroxybutyl (meth)acrylate being particularly preferred.
[0032] The content of the hydroxyl group-containing monofunctional (meth)acrylate monomer of component (B1) in the photocurable resin composition is preferably 1 mass % or more, more preferably 5 mass % or more, since if the content is too small, the reliability of the properties required for the cured product of the photocurable resin composition in a high-temperature, high-humidity environment tends to be insufficient; if the content is too high, the polarity balance of the resin before or after curing is lost, and the resin tends to become opaque, so the content is preferably 30 mass % or less, more preferably 25 mass % or less.
[0033] The content of the hydroxyl group-containing monofunctional (meth)acrylate monomer of component (B1) in the photocurable resin composition is preferably 1 to 3000 parts by mass per 100 parts by mass of the (meth)acrylate polymer of component (A) in relation to the (meth)acrylate polymer of component (A). Within this range, an effect of maintaining high transparency under various environments can be obtained.
[0034] Specific examples of the hydroxyl-free monofunctional (meth)acrylate monomer of component (B2) include the same monomers as the hydroxyl-free (meth)acrylate monomers that can form the (meth)acrylate polymer of component (A). Among them, at least one selected from isostearyl (meth)acrylate, isodecyl (meth)acrylate, and octyl (meth)acrylate is preferred. In particular, isostearyl (meth)acrylate and isodecyl (meth)acrylate are preferred.
[0035] The content of the hydroxyl group-free monofunctional (meth)acrylate monomer of component (B2) in the photocurable resin composition is preferably 30% by mass or more, more preferably 65% by mass or more, since if it is too small the composition tends to become highly viscous, and if it is too high the composition tends to become brittle, so it is preferably 90% by mass or less, more preferably 75% by mass or less.
[0036] The content of the hydroxyl-free monofunctional (meth)acrylate monomer of component (B2) in the photocurable resin composition is preferably 54 to 9000 parts by mass per 100 parts by mass of the (meth)acrylate polymer of component (A) in relation to the (meth)acrylate polymer of component (A). Within this range, the effect of being able to exhibit high performance as an adhesive while maintaining high transparency under various environments can be obtained.
[0037] <Ingredient (C)> The photocurable resin composition of the present invention contains a hydrogen abstraction type photopolymerization initiator, preferably an intramolecular hydrogen abstraction type photopolymerization initiator, as the photopolymerization initiator, rather than an intramolecular cleavage type photopolymerization initiator such as a benzoin derivative, in order to bond the hydroxyl group-containing (meth)acrylate polymer of component (A) to a side chain of the polymer chain.
[0038] As the hydrogen abstraction type photopolymerization initiator of component (C), a known hydrogen abstraction type photopolymerization initiator can be used, for example, diaryl ketones such as benphenone, and phenyl glyoxylates such as methyl benzoyl formate. A preferred example is methyl benzoyl formate, which is non-yellowing and has high hydrogen abstraction ability.
[0039] The content of the hydrogen abstraction photopolymerization initiator of component (C) in the photocurable resin composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, since if it is too small, insufficient crosslinking tends to occur; whereas if it is too large, it tends to cause deterioration of environmental reliability, so it is preferably 10% by mass or less, more preferably 5% by mass or less.
[0040] <Ingredient (D)> The photocurable resin composition of the present invention contains a tackifier to improve the interfacial adhesion strength and extensibility of the cured product. The tackifier can be appropriately selected from known tackifiers, such as rosin-based tackifiers, hydrogenated rosin ester-based tackifiers, terpene resin-based tackifiers, aromatic modified terpene resin-based tackifiers, hydrogenated terpene resin-based tackifiers, terpene phenol resin-based tackifiers, aliphatic petroleum resin-based tackifiers, aromatic petroleum resin-based tackifiers, and alicyclic (hydrogenated) petroleum resin-based tackifiers, depending on the intended use. Preferred tackifiers include alicyclic (hydrogenated) petroleum resin-based tackifiers that are excellent in all of the characteristics of colorless transparency, tastelessness and odorlessness, heat resistance, weather resistance, and electrical properties (insulation). Particularly preferred specific tackifiers include tackifiers marketed under the trademarks ARKON (registered trademark) P90, M100, or M115 (Arakawa Chemical Industries, Ltd.).
[0041] The content of the tackifier, component (D), in the photocurable resin composition is 1 mass % or more, preferably 2 mass % or more, and more preferably 3 mass % or more, because if the content is too low, the interfacial adhesion strength of the cured product of the photocurable resin composition to glass or polycarbonate tends to be insufficient; if the content is too high, the cured product tends to become cloudy, so the content is 9 mass % or less, preferably 8 mass % or less, and more preferably 6 mass % or less.
[0042] <Ingredient (E)> The photocurable resin composition of the present invention may contain a polyfunctional (meth)acrylate monomer in order to improve the reaction rate and maintain the high-temperature elastic modulus. Specific examples of the polyfunctional (meth)acrylate monomer include bifunctional or higher (meth)acrylates such as 1,6-hexanediol diacrylate (HDDA), 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, and pentaerythritol triacrylate. These may have other functional groups such as hydroxyl groups as long as they do not impair the effects of the invention. Among them, a preferred specific example of the polyfunctional (meth)acrylate monomer is at least one selected from trimethylolpropane triacrylate, pentaerythritol triacrylate, and hydroxypivalic acid neopentyl glycol diacrylate.
[0043] The content of the polyfunctional (meth)acrylate monomer of component (E) in the photocurable resin composition is preferably 0.1% or more, more preferably 1% by mass or more, since if it is too small, the crosslinking density tends to be low, and if it is too high, the composition tends to become brittle, so it is preferably 5% by mass or less, more preferably 3% by mass or less.
[0044] <Other ingredients> In addition to the above-mentioned components (A) to (D) and, if necessary, (E), various additives can be blended into the photocurable resin composition of the present invention within the scope of not impairing the effects of the present invention. For example, as a liquid plasticizing component for reducing the cure shrinkage rate, polybutadiene-based plasticizers, polyisoprene-based plasticizers, phthalate-based plasticizers, adipate-based plasticizers, etc. can be blended. In addition, as a chain transfer agent for adjusting the molecular weight of the cured product, 2-mercaptoethanol, lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-ethylhexyl thioglycolate, 2,3-dimethylcapto-1-propanol, α-methylstyrene dimer, etc. can be blended. Furthermore, if necessary, general additives such as adhesion improvers such as silane coupling agents and antioxidants can be included.
[0045] <Viscosity characteristics of photocurable resin composition before curing> The photocurable resin composition of the present invention contains the components described above, and in order to realize good inkjet suitability under normal inkjet ejection conditions, the viscosity is adjusted to 10 mPa·s or more, preferably 15 mPa·s or more, at 25°C, and 30 mPa·s or less, preferably 20 mPa·s or less, at 60°C. If the viscosity is less than 10 mPa·s at 25°C, dripping from the inkjet nozzle is likely to occur, and if it exceeds 30 mPa·s at 60°C, non-ejection is likely to occur. The viscosity of the photocurable resin composition can be measured with a general viscoelasticity measuring device. As a specific example, it can be measured using a rheometer (Haake RheoStress600, Thermo Scientific; measurement conditions: cone rotor, φ=35 mm, rotor angle 2°, shear rate 120 / s).
[0046] The viscosity of the photocurable resin composition of the present invention can be adjusted by adjusting the type, content, etc. of each of the constituent components.
[0047] <Various properties of photocurable resin composition after curing> In order to evaluate the basic optical properties of the photocurable resin composition of the present invention as an optical material after curing, and problems such as a decrease in interfacial adhesion strength and a decrease in extensibility, it is preferable to mold the composition into a film shape with a thickness of 100 μm and observe and measure the following properties, unless otherwise specified.
[0048] (a) "Appearance of the cured product" The appearance of the cured product is visually observed as a basic optical property of the optical material, because optical materials for image display devices are required to be transparent.
[0049] (b) "Tensile storage modulus [Pa] at 25℃ and 85℃" The "tensile storage modulus", which is one aspect of dynamic viscoelastic properties, indicates that the larger the value, the stronger the elastic body, and is one of the indicators for judging the adhesion between the image display member and the light-transmitting cover member. Although there is a balance with the loss tangent tan δ described later, generally, as the "tensile storage modulus" becomes lower, the body becomes less elastic, and although there is a limit, the adhesion tends to improve accordingly. The "tensile storage modulus" can be measured with a commercially available dynamic viscoelasticity measuring device (for example, a rheometer (Haake Mars II, Thermo Scientific Co., Ltd.; measurement conditions, cone rotor, φ = 8 mm, frequency 1 Hz). Here, the reason for measuring at 25 ° C is to judge the cohesive force in a room temperature environment after lamination. In this case, the larger the value, the better. The reason for measuring at 85 ° C is to judge the cohesive force of the resin when assuming a high temperature environment.
[0050] (c) "Loss tangent tanδ at 25°C (= loss modulus / storage modulus)" The larger the value of "loss tangent tanδ", the stronger the viscous body and the better the impact absorption, and it can be measured using the above-mentioned commercially available dynamic viscoelasticity measuring device. Here, the reason for measuring at 25°C is to judge the adhesion between the image display member and the light-transmitting cover member.
[0051] (d) "Glass transition temperature [℃]" The "glass transition temperature" is the peak temperature of the measurement curve for the tensile loss modulus, which can be measured using the above-mentioned commercially available dynamic viscoelasticity measuring device. If the temperature is higher than the temperature range in which the cured product is used, the cured product tends to become brittle, and if the temperature is lower, the cured product tends to flow.
[0052] (e) "Growth rate [%]" "Elongation rate" is the length L 0 The film sample was pulled at a constant speed using a known tensile tester (length at break L 1 The above L 0 As long as the tensile modulus of elasticity (b) is within a predetermined range, the larger this value is, the better the ability to follow deformation is.
[0053] (f) "Interfacial adhesion strength [N / cm 2 ]" The larger the interfacial adhesion strength, the better the adhesion. The measurement can be performed under the following conditions. That is, a photocurable resin composition is applied to the center of one of two slide glasses, for example, with a diameter of 5 mm and an average thickness of 100 μm, and then a photocurable resin composition film is formed. The other slide glass is placed so as to be perpendicular to the other, and the photocurable resin composition film sandwiched between the two slide glasses is irradiated with ultraviolet light to cure the photocurable resin composition film, thereby obtaining a light-transmitting photo-cured resin layer as a sample for interfacial adhesion strength test, and the interfacial adhesion strength of the obtained sample can be measured using a commercially available tensile tester (e.g., Autograph AGS-X, manufactured by Shimadzu Corporation).
[0054] <Preparation of Photocurable Resin Composition> The photocurable resin composition of the present invention can be prepared by uniformly mixing the components (A) to (D) and other components that are added as necessary according to a conventional method.
[0055] <Manufacturing method for image display device> Next, the method for producing an image display device of the present invention, which includes steps (a) to (c), will be described in detail for each step with reference to the drawings. In the drawings, the same reference numbers represent the same or similar components.
[0056] <Process (a) (coating process)> First, as shown in Fig. 1, a light-transmitting cover member 1 is prepared, and as shown in Fig. 2, a photocurable resin composition 2 is applied from an inkjet nozzle 3 onto a surface 1a of the light-transmitting cover member 1 to form a photocurable resin composition film 4. The coating thickness in this case can be appropriately set depending on the surface conditions of the light-transmitting cover member 1 and the image display member, the required film properties of the cured resin layer, and the like.
[0057] The photocurable resin composition 2 may be applied multiple times to obtain a required thickness.
[0058] The light-transmitting cover member 1 may have sufficient light transmittance to allow the image formed on the image display member to be visible, and may be a plate-like or sheet-like material such as glass, acrylic resin, polyethylene terephthalate, polyethylene naphthalate, polycarbonate, etc. These materials may be subjected to a hard coat treatment, an anti-reflection treatment, etc. on one or both sides. The physical properties such as the thickness and elasticity of the light-transmitting cover member 1 may be appropriately determined depending on the purpose of use.
[0059] The light-transmitting cover member 1 also includes the above-mentioned plate-like or sheet-like material to which a position input element such as a touch pad is integrated via a known adhesive or a provisionally cured resin layer or a cured resin layer of the photocurable resin composition of the present invention.
[0060] The photocurable resin composition 2 used in this step is in a liquid state under inkjet conditions. Since a liquid is used, even if there is distortion in the surface shape of the light-transmitting cover member 1 or the surface shape of the image display member, the distortion can be cancelled.
[0061] <Process (b) (Lamination process)> 3, an image display member 5 is attached to the light-transmitting cover member 1 from the photocurable resin composition film 4 side. The attachment can be performed by applying pressure at 10°C to 80°C using a known pressure-bonding device.
[0062] Examples of the image display member 5 include a liquid crystal display panel, an organic EL display panel, a plasma display panel, and a touch panel. Here, the touch panel refers to a display element such as a liquid crystal display panel and a position input element such as a touch pad integrated together via a known adhesive or a provisionally cured resin layer or a cured resin layer of the photocurable resin composition of the present invention. Note that, when the touch pad is already integrated into the light-transmitting cover member 1, it is not necessary to employ a touch panel as the image display member 5.
[0063] <Process (c) (curing process)> Next, as shown in FIG. 4, the photocurable resin composition film 4 formed in step (b) is irradiated with ultraviolet light UV from the light-transmitting cover member 1 side to cure, and a light-transmitting photocured resin layer 6 is formed as shown in FIG. 5. This results in an image display device 100. The photocurable resin composition film 4 is cured in order to change the photocurable resin composition 2 from a liquid state to a non-flowing state, to impart adhesion to the photocured resin layer 6, and to improve the handling properties by preventing the composition from flowing even when the composition is turned upside down. The level of curing is such that the curing rate (gel fraction) of the light-transmitting photocured resin layer 6 is preferably 40% or more, more preferably 60% or more. Here, the curing rate (gel fraction) is a value defined as the ratio (consumption rate ratio) of the amount of (meth)acryloyl groups present after ultraviolet irradiation to the amount of (meth)acryloyl groups present in the photocurable resin composition 2 before ultraviolet irradiation, and the larger this value, the more the curing has progressed. The degree of light transmittance of the photocured resin layer 6 is sufficient as long as the image formed on the image display member is visible.
[0064] The curing rate (gel fraction) was measured by measuring the change in the curing rate from 1640 to 1620 cm from the baseline in the FT-IR measurement chart of the resin composition layer before ultraviolet irradiation. -1 and the absorption peak height (X) of 1640 to 1620 cm from the baseline in the FT-IR measurement chart of the resin composition layer after ultraviolet irradiation. -1 and the absorption peak height (Y) of the sample can be calculated by substituting the above-mentioned formula (1) below.
[0065]
number
[0066] Regarding the irradiation with ultraviolet light, as long as it is possible to cure the composition so that the cure rate (gel fraction) is preferably 95% or more, the type, output, cumulative light amount, and the like of the light source are not particularly limited, and known ultraviolet light irradiation photoradical polymerization process conditions for (meth)acrylate can be adopted.
[0067] The level of light transmittance of the light-cured resin layer 6 may be such that the image formed on the image display member 5 can be visually recognized.
[0068] Alternatively, instead of fully curing the photocurable resin composition all at once, the photocurable resin composition may be provisionally cured, then laminated, and then fully cured, as in the following steps (aa) to (dd).
[0069] <Process (aa) (coating process)> First, as shown in Fig. 6, a light-transmitting cover member 10 is prepared, and as shown in Fig. 7, a photocurable resin composition 20 is applied from an inkjet nozzle 30 to a surface 10a of the light-transmitting cover member 10 to form a photocurable resin composition film 40. The coating thickness in this case can be appropriately set depending on the surface conditions of the light-transmitting cover member 10 and the image display member, the required film properties of the cured resin layer, and the like.
[0070] The photocurable resin composition 20 may be applied multiple times to obtain a required thickness.
[0071] <Process (bb) (temporary curing process)> Next, as shown in FIG. 8, the photocurable resin composition film 40 applied in step (aa) is irradiated with ultraviolet light UV to temporarily cure it, thereby forming a temporarily cured resin layer 45 as shown in FIG. 9. The reason for temporarily curing is to change the photocurable resin composition 20 from a liquid state to a state where it does not flow significantly, and to improve the handleability by preventing it from flowing even when the composition is turned upside down. The level of such temporary curing is such that the cure rate (gel fraction) of the temporarily cured resin layer 45 is preferably 40% or more, more preferably 60% or more. The upper limit may be 100%, but is preferably less than 100%. More preferably, it is less than 95%.
[0072] <Process (cc) (Laminating process)> 10, the light-transmitting cover member 10 is bonded to the image display member 50 from the side of the temporarily cured resin layer 45. The bonding can be performed by applying pressure at 10°C to 80°C using a known pressure bonding device.
[0073] <Process (dd) (main curing process)> Next, as shown in Fig. 11, the provisionally cured resin layer 45 sandwiched between the image display member 50 and the light-transmitting cover member 10 is irradiated with ultraviolet light UV to fully cure. As a result, the image display member 50 and the light-transmitting cover member 10 are laminated via the light-transmitting photocurable resin layer 60 to obtain the image display device 100 (Fig. 12). Note that, if the cure rate of the provisionally cured resin layer is 100%, this step (dd) may be omitted, but it is preferable to always carry out this step in order to ensure full curing.
[0074] The reason for the main curing in this step is to sufficiently cure the provisionally cured resin layer 45 to bond and laminate the image display member 50 and the light-transmitting cover member 10. The level of such main curing is set so as not to be lower than the cure rate of the provisionally cured resin layer 45. In general, the cure rate (gel fraction) of the light-transmitting photocured resin layer 60 is set to be preferably 95% or more, more preferably 98% or more.
[0075] The level of light transparency of the light-transmitting photocurable resin layer 60 may be such that the image formed on the image display member 50 is visible. In the above steps (aa) to (dd), the photocurable resin composition is applied to the light-transmitting cover member, but it may be applied to the image display member and then the light-transmitting cover member may be laminated thereon. EXAMPLES
[0076] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The components used in the examples and comparative examples are as follows.
[0077] (Meth)acrylate polymer HITAROID® 7927 (Hitachi Chemical Co., Ltd.); MW 190,000, 170 mg KOH / g
[0078] Hydroxyl group-containing monofunctional (meth)acrylate monomer 4-HBA (4-Hydroxybutyl acrylate)
[0079] Hydroxyl-free monofunctional (meth)acrylate monomer ISTA (Isostearyl acrylate) IDA (Isodecyl Acrylate)
[0080] Multifunctional (meth)acrylate monomer PETIA (Pentaerythritol (tri / tetra)acrylate; Daicel Allnex Co., Ltd.)
[0081] Hydrogen abstraction type photoinitiator Omnirad® MBF (IGM Resins BV), methyl benzoyl formate
[0082] Examples 1 to 4, Comparative Examples 1 to 2 A photocurable resin composition was prepared by uniformly mixing the ingredients shown in Table 1. The resulting photocurable resin composition was measured for its viscosity [mPa s], a liquid property before photocuring that contributes to inkjet coatability, as described below. In addition, the appearance of the cured product, tensile storage modulus [Pa] at 25°C and 85°C, loss tangent tan δ (= loss modulus / storage modulus) at 25°C, glass transition temperature [°C], elongation [%], and interfacial adhesion strength [N / cm 2 ] was measured as described below.
[0083] <Before photocuring> (Viscosity of Photocurable Resin Composition) The viscosities of the photocurable resin composition at 25°C and 60°C were measured using a rheometer (Haake RheoStress600, Thermo Scientific; measurement conditions: cone rotor, φ=35 mm, rotor angle 2°, shear rate 120 / s). The measurement results are shown in Table 1. Regarding the inkjet coatability of the photocurable resin composition, it is desirable that the viscosity at 25°C is 10 mPa s or more and the viscosity at 60°C is 30 mPa s or less.
[0084] <After light curing> After photocuring of the photocurable resin composition, the following items were recorded: "Appearance of the cured product", "Tensile storage modulus [Pa] at 25°C and 85°C", "Loss tangent tan δ (= loss modulus / storage modulus) at 25°C", "Glass transition temperature [°C]", "Elongation [%]", "Interfacial adhesion strength [N / cm 2 ]" was observed or measured as described below.
[0085] (Appearance of the cured product) The photocurable resin composition was exposed to an ultraviolet ray irradiation device (LC-8, manufactured by Hamamatsu Photonics K.K.) with an accumulated light dose of 5000 mJ / cm 2 So, 200mW / cm 2 The photocurable resin composition was cured by irradiating it with strong ultraviolet light. The obtained cured product was visually observed to see whether it was transparent or cloudy. The observation results are shown in Table 1. An optical material for an image display device is required not to become cloudy.
[0086] (Tensile storage modulus [Pa] at 25℃ and 85℃) The photocurable resin composition was applied to a thickness of 2 mm on a release-treated PET film, and the composition was exposed to an ultraviolet ray irradiation device (LC-8, Hamamatsu Photonics K.K.) with an accumulated light dose of 5000 mJ / cm. 2 So, 200mW / cm 2The photocurable resin composition film was cured by irradiating it with strong ultraviolet light, and then peeled off from the PET film to prepare a sample film for viscoelasticity testing. The tensile storage modulus of the obtained sample film at 25°C and 85°C was measured using a viscoelasticity measuring device (DMS6100, manufactured by Seiko Instruments Inc.; measurement conditions: length = 20 mm, thickness = 2 mm, width = 10 mm, frequency 1 Hz). As an optical material for an image display device, it is desirable that the value of the tensile storage modulus is in the range of 1.0E+05 to 7.0E+05.
[0087] (Loss tangent tanδ at 25℃ (= loss modulus / storage modulus)) A sample film for viscoelasticity testing was prepared in the same manner as in the measurement of the tensile storage modulus, and the tensile loss modulus was measured using the same viscoelasticity measuring device. The ratio (%) of the value to the previously measured tensile storage modulus was calculated as the loss tangent tan δ. For optical materials for image display devices, it is desirable for the value of the loss tangent tan δ to be in the range of 1 to 2.
[0088] (Glass transition temperature "℃") A sample film for viscoelasticity testing was prepared in the same manner as in the measurement of the tensile storage modulus, and its glass transition temperature was measured using the same viscoelasticity measuring device. As an optical material for an image display device, the glass transition temperature is preferably in the range of -60 to 0°C.
[0089] (Growth rate "%") The photocurable resin composition was dropped onto a release film to a predetermined thickness, then cured by irradiating ultraviolet light, and cut to a predetermined size (for example, 1 mm, 10 mm width, 30 mm length) to prepare a sample, and its elongation was measured using a tensile tester (Tensilon, Orientec Co., Ltd.). The measurement conditions were an atmospheric temperature of 25°C and a pulling speed of 10 mm / min, and the measured value was substituted into the formula "elongation (%) = L / L0 x 100" to obtain the elongation. Here, L0 is the reference length, and L is the displacement length until breakage. For optical materials for image display devices, when the tensile storage modulus at 25°C is within the above range, it is preferably in the range of 100 to 200%. This is because the resin cured product can follow the warp of the image display member, and peeling from the interface between the resin cured product and the bonding member can be greatly suppressed.
[0090] (Interfacial adhesion strength (splitting strength) [N / cm 2 ]) Two slide glasses (40 (W) × 70 (L) × 0.4 (t) mm, model number S1112) manufactured by Matsunami Glass Industry Co., Ltd. were prepared. The photocurable resin composition was applied to the center of one of the slide glasses to a diameter of 5 mm and an average thickness of 100 μm. First, an ultraviolet irradiation device (LC-8, manufactured by Hamamatsu Photonics K.K.) was used to apply an accumulated light amount of 2000 mJ / cm. 2 So, 200mW / cm 2 The photocurable resin composition film was semi-cured by irradiating it with strong ultraviolet light, and the other slide glass was placed on the obtained semi-cured resin film so as to be perpendicular to the other slide glass. The accumulated light amount was 5000 mJ / cm for the semi-cured resin film sandwiched between the two slide glasses. 2 So, 200mW / cm 2 The photo-semi-cured resin layer was fully cured by irradiating it with strong ultraviolet light, forming a light-transmitting photo-cured resin layer. This gave a sample for adhesive strength testing. The adhesive strength of this sample was measured using a tensile tester (Autograph AGS-X, Shimadzu Corporation; test speed 5 mm / min, test temperature 85°C). The results are shown in Table 1 and Figures 13 and 14. As for optical materials, the numerical value of the interface adhesion strength to glass was 85 to 100 N / cm 2for polycarbonate, 35-45N / cm 2 It is desirable that the range is within the range of
[0091] [Table 1]
[0092] (Discussion of evaluation results) The photocurable resin compositions of Examples 1 to 4 had a hydroxyl value of 120 mgKOH / g or more, and contained a (meth)acrylate polymer having no (meth)acryloyl group, a monofunctional (meth)acrylate monomer, a hydrogen abstraction type photopolymerization initiator, and further contained 2.9 to 4.7 mass% of a tackifier in the photocurable resin composition. The photocurable resin compositions had a viscosity of 10 mPa s or more at 25°C and 30 mPa s or less at 60°C. As can be seen from Table 1 and Figures 13 and 14, the photocurable resin compositions had excellent inkjet coatability before curing and excellent interfacial adhesion strength as well as extensibility after curing.
[0093] On the other hand, the cured product of the photocurable resin composition of Comparative Example 1 did not contain a tackifier, and therefore had insufficient interfacial adhesion strength compared to the cured products of the photocurable resin compositions of Examples 1 to 4. In particular, the interfacial adhesion strength to polycarbonate was significantly reduced, and the elongation rate was also reduced. Thus, it was found that the inclusion of a tackifier in a predetermined amount range can improve the interfacial adhesion strength and extensibility.
[0094] In the case of Comparative Example 2, the cured product became cloudy because an excessive amount of tackifier was contained. [Industrial Applicability]
[0095] The photocurable resin composition of the present invention is a photocurable resin composition that is applied utilizing an inkjet coating method and does not cause problems such as decreased interfacial adhesion strength and decreased extensibility that are derived from the use of a (meth)acrylate oligomer having a (meth)acryloyl group, and is therefore useful for forming a photocured resin layer when producing an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocured resin layer. [Explanation of symbols]
[0096] 1, 10 Light-transmitting cover member 1a, 10a Surface of light-transmitting cover member 2, 20 Photocurable resin composition 3, 30 Inkjet nozzle 4, 40 Photocurable resin composition film 45 Pre-cured resin layer 5, 50 Image display member 6, 60 Photocured resin layer 100 Image display device
Claims
1. The photocurable resin composition can be applied to an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocurable resin layer formed from the photocurable resin composition, the photocurable resin composition comprising the following components (A) to (D): <Component (A)> A (meth)acrylate polymer having a hydroxyl value of 120 mgKOH / g or more and having no (meth)acryloyl group; <Component (B)> Monofunctional (meth)acrylate monomer; <Component (C)> Hydrogen abstraction type photopolymerization initiator; and <Component (D)> Tackifier; Contains The content of component (A) in the photocurable resin composition is 1 to 55% by mass, The content of component (B) in the photocurable resin composition is 30 to 90 mass %, The content of component (C) in the photocurable resin composition is 0.1 to 10 mass %, The content of component (D) in the photocurable resin composition is 1 to 9 mass %, The viscosity of the photocurable resin composition is 10 mPa·s or more at 25° C. and 30 mPa·s or less at 60° C., The photocurable resin composition does not contain an oligomer having a (meth)acryloyl group.
2. 2. The photocurable resin composition according to claim 1, wherein the content of component (D) in the photocurable resin composition is 2 to 8 mass %.
3. The content of each component in the photocurable resin composition is Component (A): 10 to 45% by mass, Component (B): 60 to 80% by mass, Component (C): 1 to 5% by mass, Component (D): 3 to 6% by mass 3. The photocurable resin composition according to claim 2, wherein
4. 4. The photocurable resin composition according to claim 1, wherein the (meth)acrylate polymer of component (A) is a copolymer of 2-hydroxyethyl acrylate and 2-ethylhexyl acrylate.
5. The photocurable resin composition according to any one of claims 1 to 4, wherein the monofunctional (meth)acrylate monomer of component (B) contains a hydroxyl group-containing monofunctional (meth)acrylate monomer of component (B1) and a hydroxyl group-free monofunctional (meth)acrylate monomer of component (B2).
6. 6. The photocurable resin composition according to claim 5, wherein the component (B1) hydroxyl group-containing monofunctional (meth)acrylate monomer is at least one member selected from the group consisting of 4-hydroxybutyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate.
7. 6. The photocurable resin composition according to claim 5, wherein the non-hydroxyl-containing monofunctional (meth)acrylate monomer of component (B2) is at least one member selected from the group consisting of isostearyl (meth)acrylate and isodecyl (meth)acrylate.
8. 8. The photocurable resin composition according to claim 1, wherein the hydrogen abstraction type photopolymerization initiator of component (C) is methylbenzoyl formate.
9. 9. The photocurable resin composition according to any one of claims 1 to 8, wherein the tackifier of component (D) is an optionally hydrogenated alicyclic petroleum resin-based tackifier.
10. Furthermore, component (E) <Component (E)> Polyfunctional (meth)acrylate monomer The photocurable resin composition according to any one of claims 1 to 9, wherein the photocurable resin composition contains 0.1 to 5 mass% of
11. 11. The photocurable resin composition according to claim 10, wherein the polyfunctional (meth)acrylate monomer of component (E) is pentaerythritol (tri / tetra)acrylate.
12. A method for producing an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocured resin layer formed from a photocurable resin composition, the method comprising the steps of: <Step (a)> A step of discharging the photocurable resin composition according to claim 1 from a nozzle of an inkjet coating device onto a surface of either an image display member or a light-transmitting cover member to form a photocurable resin composition film; <Step (b)> A step of laminating another member on the photocurable resin composition film and bonding the image display member and the light-transmitting cover member; and <Step (c)> A process of obtaining an image display device in which an image display member and a light-transmitting cover member are laminated with a photocurable resin layer by irradiating the photocurable resin composition film sandwiched between both panels with ultraviolet light to cure the film. The manufacturing method according to claim 1,
13. A method for producing an image display device in which an image display member and a light-transmitting cover member are laminated via a light-transmitting photocured resin layer formed from a photocurable resin composition, the method comprising the steps of (aa) to (dd): <Process (aa)> A step of discharging the photocurable resin composition according to claim 1 from a nozzle of an inkjet coating device onto a surface of either an image display member or a light-transmitting cover member to form a photocurable resin composition film; <Process (bb)> A step of irradiating the photocurable resin composition film with ultraviolet light to form a provisionally cured resin layer; <Process (cc)> A step of laminating another member on the provisionally cured resin layer and bonding the image display member and the light-transmitting cover member together; and <Process (dd)> A process of irradiating the temporarily cured resin layer sandwiched between the two panels with ultraviolet light to completely cure the resin, thereby obtaining an image display device in which the image display member and the light-transmitting cover member are laminated with the photocured resin layer. The manufacturing method according to claim 1,
Citation Information
Patent Citations
Ultraviolet curable resin composition for optical use
JP2012111843A
Acrylic resin composition, acrylic adhesive, adhesive sheet, double-sided adhesive sheet, adhesive for transparent electrode, touch panel and image display device, and manufacturing method of laminate containing adhesive layer
JP2013227399A
Photocurable resin composition and laminated sheet using same
JP2014162852A
Curable resin composition
JP2017210578A
Adhesive composition, adhesive, adhesive sheet, method for producing laminate with adhesive layer, image display device, and touch panel
JP2018109102A